Analisis Peran Galeri Investasi Syariah dalam Meningkatkan Jumlah Investor Milenial pada Universitas K.H A. Wahab Hasbullah Jombang - Widyaningsih, Bekti; Rahayu, Aprillia Setia (Universitas KH. A. Wahab Hasbullah, 2022)
The terms investment and stocks are certainly familiar. But from among students, investment itself is still considered unfamiliar even though there are also many students who have plunged directly in the world of investment. GIS (Sharia Investment Gallery) of K.H A.Wahab Hasbullah University is a forum and facility that will make it easier for students to be able to invest in stocks in the capital market. The role of GIS (Sharia Investment Gallery) in increasing and maintaining the number of millennial investors cannot be separated from the efforts and obstacles faced. This research is a type of qualitative field research, besides that the data collection method in this study uses observation, direct interviews and documentation methods. Based on the results of the research, the role of the GIS (Sharia Investment Gallery) in increasing and maintaining the number of millennial investors is by conducting socialization in the form of activities that attract potential millennial investors. Education about the benefits of investing in the capital market is also a way to increase and maintain the number of millennial investors. Knowledge about investment will be the starting point in starting an investment. So that later there will be no misunderstandings in investing. Sosilization about investment also continues to be carried out by the management of the GIS (Sharia Investment Gallery) of K.H A.Wahab Hasbullah University in the form of seminars and webinars by inviting speakers from successful millennials in the investment world. Which later prospective millennial investors from among students will be motivated and interested in investing.